Overexpression of endothelial β3‐adrenergic receptor induces diastolic dysfunction in rats. (9th October 2020) - Dhot, Justine; Ferron, Marine; Prat, Valentine; Persello, Antoine; Roul, David; Stévant, David; Guijarro, Damien; Piriou, Nicolas; Aillerie, Virginie; Erraud, Angélique; Toumaniantz, Gilles; Erfanian, Morteza; et al.
Abstract: Aims: Diastolic dysfunction is common in cardiovascular diseases, particularly in the case of heart failure with preserved ejection fraction. The challenge is to develop adequate animal models to envision human therapies in the future. It has been hypothesized that this diastolic dysfunction is linked to alterations in the nitric oxide ( NO) pathway. To investigate this issue further, we investigated the cardiac functions of a transgenic rat model (Tgβ3 ) that overexpresses the human β3 ‐adrenoceptor (hβ3 ‐AR) in the endothelium with the underlying rationale that the NO pathway should be stimulated in the endothelium. Methods and results: Transgenic rats (Tgβ3 ) that express hβ3 ‐AR under the control of intercellular adhesion molecule 2 promoter were developed for a specific expression in endothelial cells. Transcriptomic analyses were performed on left ventricular tissue from 45‐week‐old rats. Among all altered genes, we focus on NO synthase expression and endothelial function with arterial reactivity and evaluation of NO and O2 − production. Cardiac function was characterized by echocardiography, invasive haemodynamic studies, and working heart studies. Transcriptome analyses illustrate that several key genes are regulated by the hβ3 ‐AR overexpression. Overexpression of hβ3 ‐AR leads to a reduction of Nos3 mRNA expression (−72%; P < 0.05) associated with a decrease in protein expression (−19%; P < 0.05). Concentration‐dependent vasodilation to isoproterenol was significantly reduced in Tgβ3 aorta (−10%; P < 0.05), while NO and O2 − production was increased. In the same time, Tgβ3 rats display progressively increasing diastolic dysfunction with age, as shown by an increase in the E/A filing ratio [1.15 ± 0.01 (wild type, WT) vs. 1.33 ± 0.04 (Tgβ3 ); P < 0.05] and in left ventricular end‐diastolic pressure [5.57 ± 1.23 mmHg (WT) vs. 11.68 ± 1.11 mmHg (Tgβ3 ); P < 0.05]. In isolated working hearts, diastolic stress using increasing preload levels led to a 20% decrease in aortic flow [55.4 ± 1.9 mL/min (WT) vs. 45.8 ± 2.5 mL/min (Tgβ3 ); P < 0.05]. Conclusions: The Tgβ3 rat model displays the expected increase in NO production upon ageing and develops diastolic dysfunction. These findings provide a further link between endothelial and cardiac dysfunction. This rat model should be valuable for future preclinical evaluation of candidate drugs aimed at correcting diastolic dysfunction.